Drivers of Hospital Length of Stay in Medicaid and Commercially Insured Mother-Infant Pairs With a Diagnosis of Neonatal Abstinence Syndrome. Issue 12 (December 2019) - Parlett, Lauren; Agiro, Abiy; Brown, Susan; Wilt, Mary; Portzline, Amy; Verburg, Jacqueline; Shea, Karen; DeVries, Andrea
Abstract : Background: The occurrence of neonatal abstinence syndrome (NAS) mirrors the growing opioid epidemic in the United States. As Medicaid covers a majority of cases, the commercially insured population has largely been ignored for NAS risk. Objective: The objective of this study was to examine Medicaid and commercially insured mother-infant pairs to determine demographic and clinical characteristics associated with NAS length of stay (LOS). Research Design: This observational, descriptive case-series study utilized administrative claims from HealthCore Integrated Research Database to measure maternal characteristics for 6 months before delivery, and neonatal characteristics and health care service utilization for 3 months after NAS diagnosis. Bootstrapped regressions were used to model LOS. Results: The sample included 1807 mother-infant pairs. Most infants (79%) had Medicaid coverage (Medicaid: N=1419; Commercial: N=388). Although all infants had NAS, Medicaid-insured mothers had more prevalent drug abuse (70.8% vs. 41.0%; P <0.0001), but fewer used prescription opioids (45.3% vs. 60.8%; P <0.0001) compared with commercially insured mothers. Commercially insured infants were sicker, with a higher prevalence of complex chronic conditions, and yet Medicaid-insured infants were admitted to neonatal intensive care unit at a much higher rate (91.1% vs. 78.9%; P <0.0001). After adjustment, neonatal intensive care unit admission (+6.7 d, 95% confidence interval: 4.5–9.3) and chronic complex conditions (+5.2 d, 95% confidence interval: 3.8–6.6) contributed most to LOS. Conclusion: A re-evaluation of obstetrical management towards a focus on the history of possible opioid and substance use regardless of insurance type and demographic background might inform efforts to reduce LOS. Abstract : Supplemental Digital Content is available in the text.